The Importance of Public Relation for Sustainability: Application of Peace Journalism in the Corporate Sector - Hidayat, Rachmat (The Indonesian Forestry Certification Cooperation, 2022)
This article consists of research that examines the importance of public relations’ role in a company in achieving sustainability. This research was conducted with qualitative method towards cases of several forest plantation companies in Indonesia, including PT Arara Abadi in Riau (Sinarmas Group), PT Wirakarya Sakti in Jambi (Sinarmas Group), PT Adindo Hutani Lestari in North Kalimantan (RAPP Group, Soekanto Tanoto) and PT Toba Pulp Lestari (RAPP Group, Tanoto). The non-optimal role of public relations creates communication gaps when informing a company's policies. This research found the importance of implementing peace journalism approach with an environmental communication model in overcoming the gaps in public understanding and the gaps in forming a public opinion that is built in the media (online). The cause is that the role of public relations lacks optimization in practicing the environmental communication model related to reporting with a peace journalism approach.